The m6A Readers YTHDF1 and YTHDF2 Synergistically Control Cerebellar Parallel Fiber Growth by Regulating Local Translation of the Key Wnt5a Signaling Components in Axons - Jun Yu (Wiley, 2021)
Abstract Messenger RNA m6A modification is shown to regulate local translation in axons. However, how the m6A codes in axonal mRNAs are read and decoded by the m6A reader proteins is still unknown. Here, it is found that the m6A readers YTHDF1 and YTHDF2 are both expressed in cerebellar granule cells (GCs) and their axons. Knockdown (KD) of YTHDF1 or YTHDF2 significantly increases GC axon growth rates in vitro. By integrating anti‐YTHDF1&2 RIP‐Seq with the quantitative proteomic analysis or RNA‐seq after KD of YTHDF1 or YTHDF2, a group of transcripts which may mediate the regulation of GC axon growth by YTHDFs is identified. Among them, Dvl1 and Wnt5a, encoding the key components of Wnt pathway, are further found to be locally translated in axons, which are controlled by YTHDF1 and YTHDF2, respectively. Specific ablation of Ythdf1 or Ythdf2 in GCs increases parallel fiber growth, promotes synapse formation in cerebellum in vivo, and improves motor coordination ability. Together, this study identifies a mechanism by which the m6A readers YTHDF1 and YTHDF2 work synergistically on the Wnt5a pathway through regulating local translation in GC axons to control cerebellar parallel fiber development.